Caribbean and Atlantic Diaspora Dance : Igniting Citizenship - Daniel, Yvonne, 1940- (Book collections on Project MUSE., 2011)
" In Caribbean and Atlantic Diaspora Dance: Igniting Citizenship, Yvonne Daniel provides a sweeping cultural and historical examination of diaspora dance genres. In discussing relationships among African, Caribbean, and other diasporic dances, Daniel investigates social dances brought to the islands by Europeans and Africans, including quadrilles and drum-dances as well as popular dances that followed, such as Carnival parading, Pan-Caribbean danzas, rumba, merengue, mambo, reggae, and zouk. Daniel reviews sacred dance and closely documents combat dances, such as Martinican ladja, Trinidadian kalinda, and Cuban juego de man̕. In drawing on scores of performers and consultants from the region as well as on her own professional dance experience and acumen, Daniel adeptly places Caribbean dance in the context of cultural and economic globalization, connecting local practices to transnational and global processes and emphasizing the important role of dance in critical regional tourism"--Provided by publisher.